A rare cause for discomfort of the legs - Hofer, T. (Phlebologie, 2009)
This paper presents two women who visited the phlebology surgery in the opinion that varices would be responsible for their symptoms. Patient 1 complained of nocturnal pain that radiated from the posterior surface of the left thigh to the anterior and lateral surfaces of the knee and lateral aspect of the calf. This pain occurred whenever she changed position. Patient 2 felt numbness in her right foot and an annoying burning sensation in her right heel. She was known to have lumbar discopathy and stenosis of the spinal canal which however, according to neurological diagnosis, could not explain the symptoms. On clinical examination neither had visible nor palpable varices, nor any recognisable dermal signs of venous hypertension. However, it was conspicuous that the left foot of patient 1 barely reached the floor when she was sitting down. In patient 2 the circumference of the right calf was increased by 2 cm.In both cases a coarse, circumscribed thickening was palpable deep in the posterior surface of the thigh (patient 1) and the proximal calf (patient 2). This was responsible for the asymmetrical posture in sitting of patient 1. Doppler/duplex sonography did not reveal any pathological findings in either patient. Thanks to MRI scans the cause in both cases was found to be a subfascial tumour that was displacing the musculature, thus compressing nervous structures; once in the thigh (patient 1: 600 g), once in the calf (patient 2: 200 g). In both women the symptoms disappeared after surgical extirpation of the clinically and histologically verified lipomas.
Keywords: Leg discomfort; varicose vein; neural compression; giant lipoma; thigh; calf